Integrasi Metode IPMS dan SMART System Dalam Pengukuran Kinerja Perguruan Tingi - Petir Papilo (Jurnal Teknik Industri, 2012)
This study aimed to determine the level of achievement of the organization, performance in education, especially within the scope of a faculty. By using this IPMS method, it has been established over 32 objective strategy to be achieved that were summarized into 9 (nine) aspects are perspectives that exist on the SMART System Model. From the analysis of the priorities that had been made, there are five main factors that became the focus of attention and a critical indicator of success in achieving the vision and mission set by the “X” Faculty.From the measurements that had been performed Faculty performance index values were 3.72 level. Referod to a standard level of achievement, it could be concluded that the achievement of the Faculty “X”, was still far from the expected target, at the 8 to 9 level.